Financing potential in Portuguese small and medium-sized enterprises - Morgado, Ana Vitória Gomes (2019)
The main purpose of this dissertation is to show the main sources of financing that SMEs have access to, given that these companies represent most of the Portuguese business community. Secondly, it is intended to verify what types of financing and financial instruments companies use to obtain the desired financing and what is the purpose of the company in obtaining such financing. For that purpose a questionnaire is applied to companies, Finally, the study intends to understand if SMEs use or are aware of the help provided by public institutions, such as IAPMEI. With both the literature review and the application of the questionnaires the study concludes that the companies do not use nor exploit all the market hypotheses available for their financing. Despite the wide range of opportunities given by banks and other financial institutions, companies stick to the method they know, which is also the most common, the bank financing.